Sikap Keagamaan Dan Potensi Radikalisme Agama Mahasiswa Perguruan Tinggi Agama - Wahid Khozin (Badan Litbang dan Diklat Kementerian Agama RI, 2013)
This writing is based on the research result data of the Radicalism Potencies in the Islamic Higher Education (Perguruan Tinggi Agama/PTA) students. This study uses the survey approaches which are done in 10 provinces with the target population consists of PTA students of Islam, Catholic, Christian, Hindu and Buddha, with the aims to know the understanding and social-politics of the religious attitudes, as well as the radicalism potencies in PTA. The result shows: 1) the tendency of the radical religious attitudes of the PTA Students, but it is still on the lower level; 2) the tendency of sectarian way of thinking especially in the relation of religious norm positivization on social-state life; 3) the tendency of religious-political orientation; 4) the tendency of the support toward the use of violent media to actualize the religious messages.Â Tulisan ini berbasis data hasil penelitian tentang Potensi Radikalisme di Kalangan mahasiswa pendidikan tinggi agama (PTA). Studi ini menggunakan pendekatan survei yang dilakukan di 10 provinsi dengan populasi target adalah mahasiswa PTA Islam, Katolik, Kristen, Hindu dan Buddha, dengan tujuan mengetahui pemahaman dan sikap social-politik keagamaan, serta potensi radikalisme di kalangan mahasiswa di PTA. Hasilnya menunjukkan: 1) adanya kecenderungan sikap keagamaan yang radikal mahasiswa PTA, tetapi masih taraf rendah; 2) adanya kecenderungan cara berpikir sektarian terutama berkaitan dengan positivisasi norma agama dalam kehidupan kenegaraan; 3) adanya kecenderungan orientasi politik keagamaan; dan 4) adanya kecenderungan dukungan terhadap penggunaan media kekerasan untuk mengaktualisasikan pesan-pesan agama.